A ineficiência da execução fiscal no estado de Goiás como situação-problema na abordagem direito e politicas públicas - Diniz, Raimundo Nonato Pereira (2020)
This study examines tax enforcement inefficiency phenomenon in the State of Goiás, with the aim of understanding currently adopted procedural and administrative practices and legal arrangements which regulate them and also of contributing to the formulation of good practices and adjustments in these arrangements, which may allow efficiency gains in terms of increased revenue and procedural speed. For the organization of this study, the theoretical reference is based on Law and Public Policy Approach and the adopted methodologies were bibliographic research and descriptive statistics. In the end, it was concluded that tax enforcement inefficiency in the State of Goiás is associated with tax enforcement actions nonselective filing, which leads to judicial collection of credits without indicative characteristics of their recovery viability. To impact this scenario, it was proposed to issue a normative act that exempts tax enforcement actions filing in relation to non-viable credits and authorizes the consensual resolution of cases as alternative measures to recover credits from the state's active debt, as well as to adopt strategic management practices at scale, based on previous classification of credits.